Respuesta :

Answer:

x = 7/12

Step-by-step explanation:

Write the expression in exponential form with the base of 2

[tex]2x^{3x-3}[/tex]  = [tex]32^{3x-2}[/tex]

[tex]2^{3x-3}[/tex]  = [tex]2^{15x-10}[/tex]

Since the bases are the same, set the exponents equal

x - 3 = 15 - 10

Move variable to the left-hand side and change its sign

3x - 15x - 3 = -10

Move constant the the right-hand side and change its sign

3x - 15x = -10 + 3

Collect like terms

-12x = -10 + 3

Calculate the sum

-12x = -7

Divide both sides o the equation by -12

x = 7/12

Solution

7/12

Alternate form

x = 0.583

ACCESS MORE